Politics in Private : Love and Convictions in the French Political Consciousness - Muxel, Anne.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This book investigates the relationships between political allegiance and private relationships, and in doing so offers a fascinating insight into the way the French think about this subject.
Keywords: Social sciences; Political science; United States -- Politics and government; Cultural studies; Religion and culture; Political sociology; Personality; Social psychology